Contexts of Gender Violence in Iranian Kurdistan; Analysis of the Lived Experience Narrative of Sanandji Women - Ghaderzadeh, Asst.Prof.Omid Ghaderzadeh (Sulaimani Journal for Humanities, 2026)
One of the main social problem in Iranian Kurdistan is the spread of gender violence in the family, public spaces and official and institutional arenas. The pervasiveness and frequency of violence in the aforementioned fields has made violence a normal frequency in public opinion and the social sensitivity towards it has become sectional in nature. The present study aims to analyze the contexts of gender violence in Iranian Kurdistan through women's experience and understanding of violence.The current study intends to analyze the contexts of gender violence among a sample of Sanandji women in Iranian Kurdistan through women's experience and understanding of violence.In the current research, the narrative analysis method has been used, and interviews were conducted with 35 samples of women who had experienced violence in their lives, as well as with female clients to courts and counseling centers.Based on the findings, women have experienced violence in objective, psychological, symbolic, and institutional/structural forms in private (domestic), public, and official arenas. From the point of view of the studied women, institutional discrimination, gender socialization and deprivation of power sources have shaped the contexts and bases of gender violence against women. based on the findings, it is not possible to reduce gender violence to an individual and psychological issue and neglect the change and reform of the institutional and structural foundations of violence.
Keywords: Gender Violence; Social Exclusion; Institutional Violence; Symbolic Violence